Creativity and Local Wisdom: Community Empowerment in Developing Traditions, Arts, and Culture in the Giyanti Wonosobo Hills Area in Central Java - Haryanto, Sri; Sukawi, Sukawi; Rozi, Fathur (Abdimas Indonesian Journal, 2024)
The community service program "Community Empowerment in Developing Traditions, Arts, and Culture in the Giyanti Wonosobo Hilly Area" is a strategic initiative that aims to increase community awareness and active participation in efforts to preserve and develop rich local cultural heritage. The Giyanti Hills region, known for its unique diversity of traditions, arts, and cultures, is now facing serious challenges due to the negative impact of rapid modernization. This program focuses on preservation and empowering the community to act as agents of change in maintaining and developing existing cultural values. Through a series of activities involving education, training, and cross-sector collaboration, it is hoped that people can understand the importance of their cultural identity and integrate it into their daily lives. This service is expected to create a strong collective awareness, encourage active participation in arts and cultural activities, and strengthen social cohesion among community members. The success of this initiative will have a significant positive impact not only on the local community but also on the development of sustainable tourism that respects and uplifts local cultural values.